Jawhar and waqf development in Malaysia / Dahlia Ibrahim ... [et al.] - Ibrahim, Dahlia; Mohamed Isa, Zuraidah; Ali, Norhidayah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Waqf is an Islamic instrument that can give positive impact in the economic development of a society; especially its role to improve the quality living of the Muslims. In Malaysia, the State Religious Councils (SIRCs) carry the responsibility as trustees to register, regulate, monitor and manage waqf as to promote the socioeconomic justice of the waqf institution. However, there are no clear guidelines as how the SIRCs should manage the waqf. In specific, some waqf officials do not put development of waqf as their priority. Hence, managing waqf is a complex task. It is not unfamiliar to hear about the difficulty in developing unproductive waqf properties. Not to say, no single effort has been taken up to effectively develop waqf, but most attempts seem to be fruitless. To rectify this situation, the Malaysian government took a big step and established an entity called Department of Wakaf, Zakat and Haj (Jabatan Wakaf, Zakat dan Haji also known as JAWHAR). The Malaysian Former Prime Minister, Abdullah Bin Badawi, announced the establishment of JAWHAR on 27th March 2004 (Mohd Salleh & Muhammad, 2008).